E-Learning and Covid-19 Pandemic Advantages, Challenges and Recommendations: An overview - Khalleefah, Zaynab Ahmed (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2022)
The emergence of the Corona Virus disease has created several emergencies in the world leading to the concerned departments face thousands of challenges to cope up this world-shaking event. The turning point of on campus and E-learning occurred soon after the lockdown was announced on global level and everything was forced to move online to reduce the spread of the virus. The world fought the battle of Corona Virus in every department, including the educational sector being hit the hardest. The people willingly and unwillingly moved to the process of E-Learning in order to remove the obstacle that Covid created in the way of education. This paper aims to talk about the pivotal relationship between Covid 19 and the important role that E-learning has played along with the challenges and recommendations for building a better relationship between the e-learning process and educational development.